Perception of the Periodontitis Patients on Oral Health-Related Quality of Life (OHQoL): Does Socio-demographic factors influence on it? A pilot study among the Patients from Polyclinic, Kulliyyah of Dentistry, International Islamic University, Malaysia - Yaacob, Munirah; Tin, Myo Han; Abllah, Zurainie; A. Wahab, Siti Munawwarah; M. Sham, Siti Atiqah (2014)
Objectives: To investigate the socio-demographic influences on OHQoL perceived by periodontitis patients.